STUDI PENERAPAN DESAIN UNIVERSAL PADA RESTORAN BONCAFE DI SURABAYA - Limantoro, Carolina (Institute of Research and Community Outreach - Petra Christian University, 2014)
Restaurant is a place where people meet for various purposes. Restaurants should therefore give universal facilities that can be utilized by everyone. Design plays an important factor in the operation and services that restaurants provide. The application of a universal design to the Boncafe restaurant can ease customers who have physical disabilities, of a certain age, or even a certain gender. This research uses the qualitative descriptive and comparative methods, followed by a classification analysis method, and finally by design solution suggestion method. By using universal design parameters based on universal design principles, the factors involved in universal design application can be clarified to identify the problems associated with the application of universal design in the Boncafe restaurant. Research shows that the application of universal design in the Boncafe restaurant has been adequately optimal, only showing little problems in small public areas of the restaurant. Solutions are offered according to the highlight problems in order to maximize the application of a universal design..